Pengaruh Pengelolaan Kopi Robusta Terhadap Kondisi Sosial Ekonomi Masyarakat di HKM Binawana Register 45B Desa Tri Budisukur, Kecamatan Kebun Tebu, Lampung Barat, Lampung - Ricat Rawanda; Redi Mutama; Moch Herman Surya; Bainah Sari Dewi (Journal of People, Forest and Environment, 2021)
Robusta coffee is a type of coffee plant with the scientific name Coffea canephora. Robusta name is taken from the word "robust", a term in English which means strong. The purpose of this study was the effect of robusta coffee management on social, economic and cultural aspects at HKM Binawana Register 45B Tri Budisukur Village, Kebun Tebu District, West Lampung, Lampung. The research analysis used descriptive qualitative. Data collection methods were interviews with 40 respondents conducted in July-August 2020, field observations and documentation studies. The results showed that coffee management was influenced by the characteristics of the respondents, including age, education level, number of dependents, cultivated land area and income level. Public perception regarding coffee management at HKm Binawana states that around 62.5% or 25 respondents strongly agree that the management of robusta coffee at HKm Binawana can meet the needs of the local community, around 70% or 30 respondents strongly agree that the management of Robusta coffee at HKm Binawana can provide employment for the surrounding community, around 87.5% or 35 respondents harvest coffee 1-3 times a year, and around 62.5% or 25 respondents have managed coffee plants for one generation. Keywords:  HKm Binawana; Robusta coffee; The influence of coffee management on the socio-economy.